Gallbladder polypoid lesions are inaccurately reported and undermanaged: a retrospective study of the management of gallbladder polypoid lesions detected at ultrasound in symptomatic patients during a 36-month period. Issue 6 (June 2019) - Abdullah, A.A.N.; Rangaraj, A.; Rashid, M.; Puw-Jones, R.; Rasheed, A.
Abstract : AIM: To investigate whether gallbladder polypoid lesions (GPL) are accurately reported and managed by radiologists, sonographers, general practitioners (GPs) and surgeons. MATERIALS AND METHODS: Consecutive abdominal ultrasound examinations indicating GPL in symptomatic patients performed during 2011–2013 were captured and analysed. The study comprised 244 patients who satisfied the inclusion criteria. RESULTS: Of the ultrasound reports retrieved, 238/244 reports (98%) erroneously described the polypoid lesions as polyps. One hundred and thirty-two of the 244 (54%) reports recommended follow-up, 5/244 (2%) recommended no follow-up, 35/244 (14%) deemed the findings insignificant, and 72/244 (30%) did not comment. Regarding GP referral, 57/184 (31%) patients were correctly referred to general surgeons, 20/184 (11%) to gastroenterologists, and 107/184 (58%) were not referred to secondary care. Forty-three of the 244 patients (18%) underwent cholecystectomy. Regarding subsequent biliary presentations, 63/244 patients (26%) presented at a later date with biliary symptoms; 13/63 (21%) of these eventually had cholecystectomies with 2/13 (15%) experiencing potentially life-threatening pancreatitis episodes. Regarding the surgical approach, differences were observed in the way individual surgeons managed polypoid lesions, with some veering towards cholecystectomy, others towards follow-up ultrasound, and some towards discharge. CONCLUSION: GPL tend to be misreported by radiologists and sonographers, unappreciated by GPs, and variably managed by surgeons. These factors delay definitive therapy and seem to contribute to future biliary presentations. A fresh educational approach is required to raise awareness among radiologists, sonographers, and GPs regarding the clinical relevance and possible representations of GPL, and a uniform strategy is needed for managing GPL. Highlights: Gallbladder polypoid lesions (GPL) tend to be misreported by radiologists and sonographers as 'polyps'. GPL are subsequently unappreciated by GPs who lean towards discharging these patients. 26% of our patients thus re-presented in the future with the same symptoms. Even with surgical referral there is variable management amongst surgeons. A fresh educational approach is required to raise awareness regarding possible representations of GPL.